The Influence of Product Design, Product Quality, and Price on Purchase Decisions at UD. Satria Muda Pratama in Makassar City - Hanim, Nuha Fauziyah; Mustari, Mustari; Ahmad, Muh. Ihsan Said; Hasan, Muhammad; Nurdiana, Nurdiana (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine how the influence of product design, product quality, and price on the purchase decision of Calligraphy products at UD. Satria Muda Pratama in Makassar City. UD. Satria Muda Pratama in marketing its products has made various efforts so that its products are in demand by the public. Calligraphy wall decoration product from UD. Satria Muda Pratama has various shapes, sizes, and verses taken from the Qur'an. The method that the researchers used in this study was quantitative, in collecting data here based on a questionnaire. The sample of this research is 83 respondents, analyzed using multiple linear regression. Based on the research results, customers of UD. Satria Muda Pratama in Makassar City who made the purchase, simultaneously the three independent variables had a significant effect on their decision to buy calligraphy products. The independent variable, namely the price variable, has a significant effect on the decision to purchase calligraphy products at UD. Satria Muda Pratama in Makassar City, but the product design and product quality variables have no effect and are partially significant on the purchasing decision of calligraphy products at UD. Satria Muda Pratama in Makassar City.